2015
DOI: 10.1080/15384101.2015.1087620
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine contributes to maintenance of mouse embryonic stem cell self-renewal through PKC-dependent downregulation of HDAC1 and DNMT1/3a

Abstract: (2015) Glutamine contributes to maintenance of mouse embryonic stem cell self-renewal through PKCdependent downregulation of HDAC1 and DNMT1/3a, Cell Cycle, 14:20, 3292-3305, DOI: 10.1080/15384101.2015 Although glutamine (Gln) is not an essential amino acid, it is considered a critical substrate in many key metabolic processes that control a variety of physiological functions and are involved in regulating early embryonic development. Thus, we investigated the effect of Gln on regulation of mouse embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…In addition, metabolic flux of L-Pro and L-Gln also play key roles in ESC fate including, in particular, through molecular mechanisms that alter the epigenetic landscape at both the histone and DNA levels (Comes et al, 2013;Carey et al, 2015;Ryu et al, 2015). To what extent these mechanisms play a role in improvements in pre-implantation development by L-Pro or L-Gln remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metabolic flux of L-Pro and L-Gln also play key roles in ESC fate including, in particular, through molecular mechanisms that alter the epigenetic landscape at both the histone and DNA levels (Comes et al, 2013;Carey et al, 2015;Ryu et al, 2015). To what extent these mechanisms play a role in improvements in pre-implantation development by L-Pro or L-Gln remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Ryu et al. have reported that Gln is an important factor in regulating maintenance of mouse ESCs through transcription regulation via the Akt, PKCe, and mTOR signalling pathways [ 95 ]; while Krall et al. have revealed that Asn is a powerful regulator of cell amino acid homeostasis; therefore it controls mTOR complex 1 (mTORC1) activation and cellular anabolic metabolism and proliferation [ 91 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…The regulation of desmosomal assembly by DSG1B, DSG2, and PKP1 not only enforces cell surface adhesion contacts between ECs but also regulates the cell signaling events in the cytoplasm and nucleus. DSG2 regulates actin assembly in ECs and affects proliferation via modulation of EGFR signaling [ 43 , 44 ]. PKP1 associates with eukaryotic translation initiation factor 4A1 to stimulate protein translation [ 45 ] and loss of PKP1 is linked to prostate cancer proliferation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, it was noted that NOTCH blockade modulated the expression of multiple genes regulating glutamate metabolism, including glutaminase and several glutamate transporters [ 55 ]. Tight regulation of glutaminase activity and glutamate metabolism are vital features of both stem cell function and tumor survival [ 11 , 30 , 44 ]. Interestingly, glutamine metabolism also regulates chromatin structure and pluripotency related transcription factors, such as OCT4, and therefore may play a pivotal role in vascular development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%